2019
DOI: 10.1007/s10750-019-3956-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring trophic niches and parasite communities of sympatric Arctic charr and brown trout populations of southern Norway

Abstract: Catchment-scale variation between lake habitats has the potential to simultaneously influence the trophic niche and parasite community of fish hosts. In this study, we investigated the trophic niche and parasite community of sympatric Arctic charr and brown trout populations from two interconnected southern Norwegian lakes at different altitudes. Arctic charr and brown trout occupied profundal and littoral habitats in each lake, respectively, whereas brown trout replaced Arctic charr in pelagic habitats of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Habitat appeared to be important in defining which parasites were most prevalent in their respective hosts. Differences in parasite community by habitat have previously been found in charr (Henricson & Nyman 1976;Frandsen et al 1989;Dorucu et al 1995;Knudsen et al 1997;Siwertsson et al 2016;Paterson et al 2019) and whitefish (Knudsen et al 2003;Karvonen et al 2013). When modelling individual parasite abundances, increasing abundances by age and size of the fish host were most commonly found in our study.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Habitat appeared to be important in defining which parasites were most prevalent in their respective hosts. Differences in parasite community by habitat have previously been found in charr (Henricson & Nyman 1976;Frandsen et al 1989;Dorucu et al 1995;Knudsen et al 1997;Siwertsson et al 2016;Paterson et al 2019) and whitefish (Knudsen et al 2003;Karvonen et al 2013). When modelling individual parasite abundances, increasing abundances by age and size of the fish host were most commonly found in our study.…”
Section: Discussionsupporting
confidence: 74%
“…Studies on parasites of freshwater fish in southern Norway have mainly been conducted during the 1950s to 1970s, and focused on the parasites development and lifespan (Lien 1970), single parasitehost interactions (Halvorsen 1970), the occurrence of parasites (Vik 1959(Vik , 1963Borgström & Lien 1973), and the occurrence of parasites combined with seasonal variations in abundance (Halvorsen 1968(Halvorsen , 1972Skorping 1977Skorping , 1981Andersen 1978). However, there is one recent publication investigating parasite community structure and abundance related to trophic niche and habitat in southern Norway (Paterson et al 2019). In this study, we have explored factors determining the abundance of numerous macroparasites in three species of freshwater fish, Arctic charr, Salvelinus alpinus (Linnaeus, 1758), hereafter: charr, European perch, Perca fluviatilis Linnaeus, 1758, hereafter: perch and European whitefish, Coregonus lavaretus (Linnaeus, 1758), hereafter: whitefish, in a large, oligotrophic lake in southern Norway.…”
Section: Fishmentioning
confidence: 99%
“…Third, Henriksen et al (2019) found that growth rate of Arctic charr was linearly related to abundance of a less harmful parasite, Crepidostomum spp., and non-linearly related to abundance of a more harmful parasite, Eubothrium salvelini (Schrank 1790), perhaps because the negative effect of a high-cost parasite was outweighed by the energy gained from feeding on the intermediate host. Fourth, Paterson et al (2019) found that habitat-restricted Arctic charr and littoral brown trout populations were surprisingly similar in trophic niches and parasite communities in two interconnected southern Norwegian lakes that differed in altitude. Fifth, Moccetti et al (2019) investigated parallelism in the trophic niches of polymorphic populations of Arctic charr in similar sub-Arctic lakes of northern Norway.…”
Section: Trophic Ecologymentioning
confidence: 93%
“…The breadth of a host's trophic niche has long been associated with structuring helminth infections. For instance, greater diet breadth increases potential encounter with parasite intermediate hosts, therefore leading to higher parasite abundance and taxon richness (Lagrue et al, 2011;Paterson et al, 2019). In a recent metanalysis, Gutiérrez et al (2019) found positive associations between trophic niche breadth and trophically transmitted helminths in birds.…”
Section: Introductionmentioning
confidence: 99%